(untitled) (Journal of Global Accounting, 2024)
The study examined the mediating effect of foreign ownership on the relationship between intellectual capital and firm value of non-finance firms in Nigeria. The study specifically examined how foreign ownership mediates the effect human capital management, structural capital management, capital employed management and relational capital management on market value of shares. The study adopted the ex-post facto research design; as the goal was not to manipulate any variable but rather to establish effect and mediation. The population comprised listed non-finance firms and the sample restricted to a purposive sample of thirty-one (31) firms whose annual reports were accessible and contained the needed data for the period of 11 years from 2013-2023 which was the time scope of this study. The data were analysed using the structural equation model. The results showed foreign ownership does not significantly mediate the effect of human capital management and structural capital management on market value of shares while the effect of capital employed management and relational capital management on market value of shares were significantly mediated by foreign ownership of non-finance firms in Nigeria. The study therefore concluded that apart from human capital and structural capital management, foreign ownership significantly mediates the effect of intellectual capital of firm value of non-finance firms in Nigeria. Based on these findings, the study recommended among others that management of non-finance firms need to reverse this trend in the their human capital management through hiring qualified indigenous and experienced workers, ensuring effective training of staff as at when due.